On p-adic generalized logistic dynamical system - Mukhamedov, Farrukh; Wan Rozali, Wan Nur Fairuz Alwani (IIUM Press, 2012)
Applications of p-adic numbers in p-adic mathematical physics, quantum mechanics stimulated increasing interest in the study of p-adic dynamical system. One of the interesting p-adic dynamical system is p-adic logistic map. It is known such a mapping is chaotic. In the present paper, we consider its cubic generalization, namely we study a dynamical system of the form f(x)=ax(1-x2 ) We show that for the case , the dynamical system is conjugate to the shift of symbolic dynamics.